Ліпідний обмін і порушення гормональної регуляції маси тіла у ліквідаторів аварії на ЧАЕС, хворих на цукровий діабет 2-го типу - Коваленко, О. М.; Муравйова, І. М.; Чикалова, І. Г.; Коваленко, В. В.; Пронін, О. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
We investigated the feature of lipid metabolism and hormonal disorder against the background different weight in ChNPP accident liquidators with diabetes mellitus. 101 persons (male) were investigated, their mean age were 56,4±0,8 years. Diabetes mellitus were verified in all persons with disease duration from 1 to 14 years. I group – 55 patients exposed with doses 0.25-0.9 Gy, 20 patients – exposed with doses 8.3 centiGy (II group); 26 no exposed patients in control group (III group). Overweight was substantially smaller in I group and determined in most cases as pre-obesity and obesity I grade, while in II and III group were determined obesity I2 grade. Pathological changes of lipid metabolism in I group blood tests were characterized apparent atherogenic dislipoproteinemia which was similar in II and III group in considerable contribution of triglycerides, 3-5 phenotype with high atherogenic potential. As compared with III group hyperglycemia and hypertriglyceridemia in I group combined with increase of basal level of insulin and leptin which indicated that syndrome have two components – insulin resistance and leptin resistance.